Quantitative assessment of multichannel intraluminal impedance pH and its clinical implications - Eden Koo; John O. Clarke; Boli Yang; Pankaj J. Pasricha; Nina Zhang (Physiological Reports, 2022)
Abstract We sought to quantify the characteristics of acid reflux episodes in patients with extraesophageal GERD symptoms (EES), hiatal hernia (HH), and erosive esophagitis (EroE) using multichannel intraluminal impedance pH (MII‐pH) and investigate the correlation between impedance parameters and high resolution esophageal manometry (HREM). This was a retrospective analysis of esophageal manometric and impedance data inpatients with typical GERD symptoms who underwent both HREM and 24 h MII‐pH tests. Within the three patient subgroups, we evaluated impedance metrics such as average height of reflux, total duration of reflux, maximum duration of reflux, average pH, and average area of reflux. We also introduce a novel composite reflux index (CRI) metric, which is a measure of reflux height, duration, and acidity. Patients with EES exhibited a 29.3% increase in average height of reflux, compared to non‐EES patients (p < 0.01); the average height of reflux was found to be an independent predictor of EES (p < 0.01). Patients with HH showed a 190% longer total reflux duration (p < 0.01, vs. non‐HH patients). Total reflux duration was twice as long in EroE patients compared to those without (p = 0.02). Average CRI was significantly different within all three subgroup comparisons (p < 0.01). Impedance metrics shared weak negative correlations with lower esophageal sphincter (LES) rest pressure and distal contractile integral (DCI), and weak positive correlations with % absent peristalsis (p < 0.05 to p < 0.01 for various parameters). Quantitative impedance metrics provide useful insight into the pathophysiology of reflux in patients with EES, HH, and EroE.